Differential attractiveness of induced odors emitted by eight maize varieties for the parasitoid Cotesia marginiventris: Is quality or quantity important? - Hoballah, Maria Elena; Tamo, Cristina; Turlings, Ted (My University, 2002)
Herbivore-induced plant volatiles can function as indirect defense signals that attract natural enemies of herbivores. Several parasitoids are known to exploit these plant-provided cues to locate their hosts. One such parasitoid is the generalist Cotesia marginiventris, which is, among others, attracted to maize volatiles induced by caterpillar damage. Maize plants can be induced to produce the same blend of attractive volatiles by treating them with regurgitant of Spodoptera species. We collected and analyzed the regurgitant-induced emissions of two plant species (cowpea and maize) and of eight Mexican maize varieties and found significant differences among their volatile emissions, both in terms of total quantity and the quality of the blends. In a Y-tube olfactometer, the odors of the same artificially induced plant species and Mexican varieties were offered in dual choice experiments to naive mated females of C. marginiventris. Wasps preferred cowpea over maize odor and, in 3 of 12 combinations with the maize varieties, they showed a preference for the odors of one of the varieties. A comparison of the odor collection with results from the behavioral assays indicates that not only the quantity of the volatile emissions, but also the quality (composition) of the volatile blends is important for attraction of C. marginiventris. The results are discussed in the context of the possibility of breeding crop varieties that are particularly attractive to parasitoids.
Keywords: induced plant volatiles; parasitoid; olfactometer; Cotesia; marginiventris; Spodoptera littoralis; Zea mays; Vigna unguiculata; parasitoid attraction; odor variability; MICROPLITIS-CROCEIPES CRESSON; PREDATOR-PREY INTERACTIONS; INDUCED; VOLATILE EMISSIONS; HOST-SEARCHING BEHAVIOR; INDUCED PLANT VOLATILES; AIRBORNE SEMIOCHEMICALS; SPODOPTERA-FRUGIPERDA; RUBECULA HYMENOPTERA; FORAGING STRATEGIES; PERILLUS-BIOCULATUS